Ampelopsin inhibits high glucose‐induced extracellular matrix accumulation and oxidative stress in mesangial cells through activating the Nrf2/HO‐1 pathway. (10th March 2020) - Dong, Chunping; Wu, Guifu; Li, Hui; Qiao, Yuan; Gao, Shan
Abstract : Oxidative stress plays an important role in diabetic nephropathy (DN), which is a diabetic complication. Ampelopsin (AMP) is a natural flavonoid that has been found to possess antidiabetic and antioxidative activities. However, the effect of AMP on DN remains unclear. In this study, we aimed to evaluate the protective effect of AMP on glomerular mesangial cells (MCs) exposed to high glucose (HG). We found that AMP improved HG‐caused cell viability reduction in MCs. AMP significantly suppressed the intracellular ROS production and expression levels of ROS producing enzymes NADPH oxidase 2 (NOX2) and NOX4. Increased of NOX activity in HG‐stimulated MCs was suppressed by AMP. Pretreatment with AMP inhibited extracellular matrix (ECM) accumulation in HG‐stimulated MCs with decreased expression levels of fibronectin (FN) and collagen type IV (Col IV). Furthermore, AMP elevated the expression levels of nuclear Nrf2 and heme oxygenase‐1 (HO‐1), as well as increased the mRNA levels of Nrf2‐driven genes NAD(P)H dehydrogenase quinone‐1 (NQO‐1) and HO‐1 in HG‐treated MCs. Knockdown of Nrf2 reversed the protective effects of AMP against HG‐induced oxidative stress and EMC accumulation in MCs. In conclusion, these findings indicated that AMP protected MCs from HG‐induced oxidative damage and ECM accumulation, which might be mediated by Nrf2/HO‐1 pathway.